Determinants of Adolescent Resilience Levels in Surabaya City, East Java Province, Indonesia - Rachmayanti, Riris Diana; Dewi, Fatwa Sari Tetra; Setiyawati, Diana; Izhar, M Dody; Ramani, Andrei (Kesmas, 2025)
Assessing adolescent resilience may provide valuable insights into adult resilience. This study aimed to analyze the relationship between determinants and adolescent resilience in Surabaya City. The participants of this cross-sectional study were 277 adolescents aged 12–19 years who were in senior high school. The outcome was the resilience levels. This study's findings indicated relationships between resilience levels and stress experience (p-value = 0.01), access to mental health information (p-value = 0.00), life satisfaction (p-value = 0.00), family harmony (p-value = 0.03), presence of adults to share (p-value = 0.04), feeling safe at home, school, and community (p-value = 0.00), perception of ideal body image (p-value = 0.03), and suicidal urges (p-value = 0.00). The multivariate analysis showed that a variable related to resilience was satisfaction with life (p-value = 0.04, 95% CI 1.07–24.22). Adolescents dissatisfied with their lives had a 5.09-fold greater risk of developing into established categories of resilience. Therefore, intervention efforts are necessary to increase adolescents’ resilience levels.